Amazake made from sake cake and rice koji suppresses sebum content in differentiated hamster sebocytes and improves skin properties in humans. Issue 8 (2nd August 2020) - Maruki-Uchida, Hiroko; Sai, Masahiko; Yano, Shoichiro; Morita, Minoru; Maeda, Kazuhisa
ABSTRACT: Amazake is a traditional Japanese health drink. Here, we examined the effects of amazake on skin in cells and humans. Treatment with sake cake or rice koji suppressed intracellular lipid accumulation in differentiated hamster sebocytes, likely through the reduced expression of peroxisome proliferator-activated receptor-gamma (PPARγ) mRNA. In double-blind, placebo-controlled trial, seventeen Japanese women ingested either amazake or placebo for 4 weeks. Ingestion of the amazake decreased the sebum content compared to the placebo. The questionnaires showed improvements in "face color, " "dark circles under the eyes, " "glossy hair, " and "waking up well", only in the amazake. In accordance with the questionnaires, additional analysis revealed the change in the L* values under the eyes was statistically increased in the amazake compared to the placebo. These results indicate that amazake may decrease sebum content in cells and humans and increase the L* values under the eyes, with some additional beneficial effects in humans. GRAPHICAL ABSTRACT: uf0001 Amazake made from sake cake and rice koji suppresses sebum content and increases the L* values under the eyes.